Alternate fluffy testers for detecting and diagnosing chromosome rearrangements in Neurospora crassa. - D. D. Perkins; V. C. Pollard (Fungal Genetics Reports, 1989)
Alternate fluffy testers for detecting and diagnosing chromosome rearrangements in Neurospora crassa.